2019
DOI: 10.3389/fmicb.2019.02426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Marine Algae of Chikungunya Virus Isolated From Patients in a Recent Disease Outbreak in Rio de Janeiro

Abstract: Chikungunya virus (CHIKV) infection is one of the most challenging re-emergent diseases caused by a virus, and with no specific antiviral treatment it has now become a major public health concern. In this investigation, 25 blood samples were collected from patients with characteristic CHIKV symptoms and submitted to a virus isolation protocol, which detected 3 CHIKV isolates. These samples were evaluated by sequencing for the characterization of the strains and any homology to viruses circulating in Brazil dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The sulfated polysaccharides of seaweeds have been shown to exhibit antiviral activity against a broad spectrum of viruses. It has been reported to inhibit antiviral activity against Herpes Simplex virus (HSV) ( Gomaa and Elshoubaky, 2016 ), Human immunodeficiency virus type-1 (HIV-1) ( Besednova et al, 2019 ), chikungunya virus ( Cirne-Santos et al, 2019 ), and many other enveloped and non-enveloped viruses. Also, the antiviral activity of SPs against the currently on-going pandemic coronavirus disease 2019 (COVID-19) is reported ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfated polysaccharides of seaweeds have been shown to exhibit antiviral activity against a broad spectrum of viruses. It has been reported to inhibit antiviral activity against Herpes Simplex virus (HSV) ( Gomaa and Elshoubaky, 2016 ), Human immunodeficiency virus type-1 (HIV-1) ( Besednova et al, 2019 ), chikungunya virus ( Cirne-Santos et al, 2019 ), and many other enveloped and non-enveloped viruses. Also, the antiviral activity of SPs against the currently on-going pandemic coronavirus disease 2019 (COVID-19) is reported ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro studies revealed that seaweed extracts have anti-herpes simplex virus (HSV-1, NSV-2) [6,7], anti-human immunodeficiency virus (HIV-1) [7,8], antichikungunya virus [9], anti-enterovirus (ECHO-1) [7] properties and inactivated measles virus [10] to name a few. Extensive reviews suggest that seaweed extracts can block virus-host attachment, virus entry to the cell or inhibit the replication of several types of enveloped viruses in vitro [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A series of thioguanine-coumarins derivatives were studied, and the methoxylated coumarins [54] (21, 22 and 23) exhibited the best activities against CHIKV compared to the benzouracil coumarins (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). EC 50 values were below 13.9 µM with a significant selectivity window covering SI values between 9.37 and 21.7, whereas the molecular lipophilicity of 20, 21, 22 and 23 were between 2.97 and 3.77.…”
Section: Nitrogen Heterocycle-coumarin Hybrid Compoundsmentioning
confidence: 99%
“…CHIKV has a single-strand, positive-polarity RNA genome, whose size varies between 9.7 and 12 kb [ 13 ]. The viral particles, which are often spherical, have a diameter of 70 nm and an isometric nucleocapsid of 40 nm [ 14 ]. The proteins are encoded by two open reading frames (ORFs) in which the first two-thirds of the genome from the 5′ end is responsible for expression of the non-structural proteins (NSPs) named nsP1, nsP2, nsP3, and nsP4; whereas the last one-third located at the 3′ end codifies a subgenomic RNA that originates from three structural proteins and two peptides: capsid (C), enveloped glycoprotein 1 (E1), glycoprotein enveloped 2 (E2), E3, and 6K [ 1 , 15 , 16 ].…”
Section: Chikv Infectionmentioning
confidence: 99%
See 1 more Smart Citation